THE ROLE OF FINANCING AGRICULTURE IN NATIONAL ECONOMY DEVELOPMENT - Natalia MOCANU; Veronica MOVILEANU; Cristina TENTIUC; Mariana COLESNIC (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Besides the transition to market economy as a specific form of transformations for post socialistic countries, including the Republic of Moldova; besides the necessity to form a form model which would ensure energetic, alimentary and other kinds of vital securities needed by the country’s population, it is also necessary to create the country’s social/economic structure able to counteract all the existing and recent phenomena caused by the crisis affecting nowadays the world civilization, development of transmission mechanism of processes associated with the development of agriculture for the economic growth, in order to identity perspective strategies for agriculture in the Republic of Moldova; the development of funding policy in the context of strategies of development of enterprises; analysis of the funding policy effects on the capacity of agricultural enterprises in the Republic of Moldova; development and elaboration of a financial policy of agricultural value chain for agricultural enterprises in the Republic of Moldova; argumentation of the necessity and opportunity for the innovation promotion in the financial policy of agricultural enterprises in the Republic of Moldova.